Estrutura populacional e diversidade genética do golfinho-nariz-de-garrafa Tursiops truncatus (Montagu, 1821) na costa brasileira - Fraga, Lúcia Darsie (2016)
The bottlenose dolphin (Tursiops truncatus) has worldwide distribution in different habitats, high behavioral plasticity, and large genetic and morphological variation. In Brazil, T. truncatus occurs from north to south, yet studies of population structure of the species in the country are still restricted to certain locations. There is also a proposal based on the morphology of the existence of another species, T. gephyreus, in the southern part of the distribution, in partial sympatry with T. truncatus. The goal of this study is to assess the levels of genetic variability and population structure of the species along the Brazilian coast and also compare the results with previous morphological identification. A total of 110 samples were analyzed in six areas of occurrence on the coast of Brazil, as well as specimens from French Guiana and Arquipélago de São Pedro e São Paulo (ASPSP). After analyzing the mtDNA control region and seven microsatellite loci, we found significant population structure of the species in the two markers. The results indicate the existence of three geographically distinct genetic groups: ASPSP (comprising samples from ASPSP and the French Guiana), Northeast (from states of Pará, Ceará, Rio Grande do Norte and Bahia) and Campos and Santos Basins (from BC/BS, the states of Rio de Janeiro, São Paulo and Santa Catarina). Haplotype diversity and allelic richness of these groups were high as well as their genetic structure. Samples from the RS state comprise some individuals with high likelihood to be part of the BC/BS group and others to the Northeast group. However, several individuals comprise a much differentiated genetic group in microsatellites and with mtDNA haplotypes from a unique clade, most of them identified as T. gephyreus. Combining these results with previous studies, we conclude that the bottlenose dolphin from the southwest Atlantic Ocean consists of at least four management units: i) ASPSP; ii) Northeast; iii) BC/BS (that seems to extends at least to RS); and iv) Bahía San Antonio, Argentina. Finally, from SC state to Uruguay it seems to exists a distinct genetic entity that is not the canonical T. truncatus, but sympatric to it, and that is associated with the T. gephyreus morphology, but the picture is not clear enough to propose a formal taxonomic decision.